THE INFLUENCE FACTORS ON ATHLETE’S KNEE MUSCLES STRENGHT PART II – NUMERICAL EXAMPLES (GYMNASIUM, 2009)
The paper presents the factors that have an important impact on the strength of an athlete kneemuscle. The paper solves a statically approach of the equilibrium of a leg, emphasizing the major influencesof some variables, such as: body weight, angles of the leg with respect to earth, the length of a leg etc.The numerical results above indicate that quads need to produce much more tension than hamstringsand calves. Furthermore, the compressive force between the patella and the femur increases with increasingquads tension and increasing flexion of the knee. Repeated compressive force destroys the cartilage coatingof the articulating bone surfaces, leading to frictional resistance to the sliding motion of the kneecap duringknee flexion and extension.